Analysis of Smallholder Farmers Repayment of Bank of Agriculture Loan in Ezza South Local Government Area of Ebonyi State, Nigeria (2009-2018) - B. N, Mbam; S. U, Nwibo; C, Nwofoke; P. N, Egwu; N.E, Odoh (International Journal of Sustainable Agricultural Research, 2021)
Smallholder farmer’s repayment of Bank of Agriculture (BOA) loan in Ezza South Local Government Area of Ebonyi State was studied using 120 smallholder farmer beneficiaries selected using multistage sampling technique. Data were collected from primary source only using structured questionnaire and analyzed using both descriptive and inferential statistics. Results showed default of 32.3% as out of N333, 997,620.50 were disbursed to the farmers a total of N226, 080,887.00 were repaid. However, the socioeconomic characteristics of the loan beneficiaries contributed about 75 % (R2 = 0.754) significant influence on repayment of Bank of Agriculture loan. Meanwhile, high interest rate, excessive bureaucracy, high rate of illiteracy, late approval of loan, lack of collateral, short payback period, and low farm output were identified as the major constraints to the repayment of BOA loan. It is recommended that as a measure to promote efficient and timely repayment of BOA loans by the farmers, management of BOA should address the institutional factors such as high interest rate, excessive bureaucracy and late approval of loan, high-value collateral and short payback period that were identified as the major constraints to BOA loan repayment.